The uncertainty about the moral status of human embryos and preimplantation genetic diagnosis (in Polish) (Diametros, 2012)
In this paper I report the discussion about the argument from moral uncertainty that took place in November 2012 during the debate on the website of the Polish Bioethics Society on preimplantation genetic diagnosis (PGD). The discussion was initiated by the Statement on PGD made by the Bioethics Committee of the Polish Academy of Sciences. Here I discuss the theses of the Statement and dissenting opinions that initiated the debate, then I concentrate on the following issues: (I) the permissibility of using the tools of decision theory in situations of moral uncertainty; (II) the procedure of decision-making by advisory boards in the face of moral uncertainty; (III) the importance of biological discoveries for the moral status of embryos; (IV) the possibility of a compromise in situations of value pluralism; (V) the relevance of moral status for the moral and legal permissibility of PDG.
Keywords: preimplantation genetic diagnosis; argument from moral uncertainty; value pluralism; decision theory; Polish Bioethics Society